EKSPLORASI, ISOLASI, DAN MORFOLOGI MIKROBA DARI GUA LEUNTIE, LHOONG, SERTA UJI PRELIMINARY POTENSIAL MICP (MICROBIALLY INDUCED CALCIUM CARBONATE PRECIPITATION) - Fazli, Rahmad Rizki; Taufiq, Luthfi Chaliqi; Zahra, Mimi; Jwita, Nova Elsa; Erlidawati, Erlidawati; Saaid, Mardiana (UIN AR-RANIRY, 2026)
Aceh province has interesting natural landscapes. Forests, seas, mountains and caves are very complete in decorating the natural landscape of Aceh. One of the famous caves is Leuntie Cave which is located in Lhoong, Aceh Besar. The structure of Leuntie Cave is very unique because it consists of cave walls made of rock and the floor layered with sea sand. The mouth of Leuntie Cave is located not far from the sea, only about 200 m from the shoreline which affects the humidity of the cave. High humidity level allows Leuntie Cave to be a potential and unique microbial habitat for isolation. This study used an experimental research method with the initial stage of exploration of Leuntiee Cave for sampling of soil and cave wall rocks, followed by isolation and screening of bacterial growth and obtained five bacterial isolates with codes BGL-1 to BGL-5. Microbial morphological identification was carried out by observing bacterial colonies and gram staining tests. Preliminary urea agar base test to see the potential in precipitating calcium carbonate (CaCO3) by producing the urease enzyme. The results of this study obtained two Leuntiee Cave bacterial isolates BGL-1 and BGL-3 which were positive for producing the urease enzyme and could be selected as MICP bio-agent candidates.